The Effect of Different Surface Treatments of Cad/Cam Sub-Structures on Microleacage of Veneering Composite Resins - Mustafa A. Zeinalabdeen (Journal of Global Pharma Technology, 2018)
Purpose: The aim of the study is to evaluate the effect of different surface treatments on the microleacage of hybrid composite resin to Lava Ultimate and Vita Enamic hybrid resin-nanoceramic CAD/CAM blocks. Materials and Methods: In this in-vitro study for each CAD/CAM block (4) samples were prepared and divided according to surface treatment to (4) groups as follows: control, 50 μm (Al2O3) airborne-particle, fem to second laser & combination of 50 μm (Al2O3) airborne-particle and femtosecond laser. One additional sample for each CAD/CAM block was prepared for each surface treatment group for SEM analysis. Filtek Z250 hybrid composite was adhered onto each sub group after application of universal single bond adhesive. Microleacage test for each sample was evaluated after (1000) thermal aging cycle. Dye penetration technique using a solution of 0.05% basic fluxin solution to evaluate microleacage between composite resin and CAD/CAM block. Results: Examination revealed that there is no microleacage occurred in any of tested groups (0). Conclusions: As a result of this study using these methods of surface treatments is expected to increase clinical success of the restorations.Key words: Micro-tensile bond strength, Surface treatment, Fem to second laser, CAD/CAM.